Cytogenetic trends in two families of the neotropical catfishes : Heptapteridae and Pseudopimelodidae (siluriformes) - González Gouveia, Juceli (2018)
Fil: González Gouveia, Juceli. Universidad Estatal de Londrina. Centro de Ciencias Biológicas. Departamento de Biología General; Brasil.